2016
DOI: 10.1124/jpet.116.233239
|View full text |Cite
|
Sign up to set email alerts
|

Protective Action of Anandamide and Its COX-2 Metabolite against L-Homocysteine-Induced NLRP3 Inflammasome Activation and Injury in Podocytes

Abstract: Recent studies have demonstrated that L-homocysteine (Hcys)-induced podocyte injury leading to glomerular damage or sclerosis is attributable to the activation of the nucleotidebinding oligomerization domain-like receptor containing pyrin domain 3 (NLRP3) inflammasome. Given the demonstrated antiinflammatory effects of endocannabinoids, the present study was designed to test whether anandamide (AEA) or its metabolites diminish NLRP3 inflammasome activation and prevent podocyte injury and associated glomerular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…It has been well-characterized that Hcys-induced NLRP3 inflammasome activation results in the activation of caspase-1 and the proteolytic cleavage of IL-1 and IL-18 into their biologically active form, which produces other damageassociated molecular patterns (5,(57)(58)(59). Inflammatory cells, such as macrophages and T-cells, may be recruited in glomeruli by these factors released by podocytes, contributing to O 2…”
Section: Downloaded Frommentioning
confidence: 99%
“…It has been well-characterized that Hcys-induced NLRP3 inflammasome activation results in the activation of caspase-1 and the proteolytic cleavage of IL-1 and IL-18 into their biologically active form, which produces other damageassociated molecular patterns (5,(57)(58)(59). Inflammatory cells, such as macrophages and T-cells, may be recruited in glomeruli by these factors released by podocytes, contributing to O 2…”
Section: Downloaded Frommentioning
confidence: 99%
“…We speculate that MCC950 might reduce inflammation by blocking the positive feedback of COX-2 on NLRP3 inflammasomes. However, NLRP3 inflammasome activation is inhibited through its COX-2 metabolite, PGE2-EA, and this effect is inhibited by celecoxib [50]. At present, the relationship between NLRP3 inflammasomes and COX-2 is not clear in PD and needs further research in the future.…”
Section: Discussionmentioning
confidence: 96%
“…AEA blocked Hcys-induced NLRP3 inflammasome activation in cultured podocytes and ameliorated podocyte dysfunction, ultimately precluding glomerular damage. 75 Therefore, while the former study demonstrated that an increase in CB 1 receptor gene expression accompanied by an upregulation in AEA and 2-AG is associated with podocyte injury, the latter study suggests that AEA exerts protective and anti-inflammatory effects in podocytes. Future studies are needed to investigate the role of EC ligands in CB receptor activation under varied conditions in renal health and disease.…”
Section: Ec System and Renal Diseasementioning
confidence: 95%
“…This is associated with signs of inflammation and podocyte injury, which manifest as decreased podocin and nephrin and increased desmin gene expression. 74 In contrast, Li et al 75 reported the protective functions of AEA following l -homocysteine (Hcys)-induced podocyte injury. AEA blocked Hcys-induced NLRP3 inflammasome activation in cultured podocytes and ameliorated podocyte dysfunction, ultimately precluding glomerular damage.…”
Section: Ec System and Renal Diseasementioning
confidence: 99%